2016
DOI: 10.1038/srep29940
|View full text |Cite
|
Sign up to set email alerts
|

Live-cell visualization of excitation energy dynamics in chloroplast thylakoid structures

Abstract: The intricate molecular processes underlying photosynthesis have long been studied using various analytic approaches. However, the three-dimensional (3D) dynamics of such photosynthetic processes remain unexplored due to technological limitations related to investigating intraorganellar mechanisms in vivo. By developing a system for high-speed 3D laser scanning confocal microscopy combined with high-sensitivity multiple-channel detection, we visualized excitation energy dynamics in thylakoid structures within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Recent studies have found that moss chloroplasts are surrounded by a peptidoglycan wall, emphasising the evolutionary position of P. patens chloroplasts as intermediate between free-living bacteria and fully domesticated plastids of higher plants 25 27 . Because of this intermediate position and its experimental advantages, P. patens chloroplasts are suitable objects for live-cell visualization and subsequent modelling 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that moss chloroplasts are surrounded by a peptidoglycan wall, emphasising the evolutionary position of P. patens chloroplasts as intermediate between free-living bacteria and fully domesticated plastids of higher plants 25 27 . Because of this intermediate position and its experimental advantages, P. patens chloroplasts are suitable objects for live-cell visualization and subsequent modelling 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Thylakoid membranes form intricate networks of grana and stroma lamellae structures that are about 5–10 µm in size. It is possible to visualize thylakoid membranes in the moss Physcomitrella patens with increased spatial resolution using 3D image deconvolution processing and determining photon-emitting positions through reverse calculation of the convolved point spread function (Iwai et al 2014, Iwai et al 2016). In this study, we applied 3D structured illumination microscopy (3D-SIM) to characterize thylakoid membranes in chloroplasts of A. thaliana and C. reinhardtii at subdiffraction resolution.…”
Section: Introductionmentioning
confidence: 99%
“…1-200 nm in near in vivo conditions and is widely applied in structural biology and soft matter sciences. Small-angle scattering complements various microscopic techniques, such as TEM (Menke, 1960;Paolillo and Paolillo, 1970;Staehelin, 1986;Austin and Staehelin, 2011;Armbruster et al, 2013;Heinz et al, 2016;Kowalewska et al, 2016;Wood et al, 2018;Kowalewska et al, 2019;Wood et al, 2019;Li et al, 2020), scanning electron microscopy (Mustárdy and Jánossy, 1979;Armbruster et al, 2013), cryo-EM (Ford et al, 2002;Kirchhoff et al, 2011;Engel et al, 2015), cryoelectron tomography (Shimoni et al, 2005;Austin and Staehelin, 2011;Daum and Kühlbrandt, 2011;Kouřil et al, 2011;Ford and Holzenburg, 2014;Bussi et al, 2019;Rast et al, 2019), atomic force microscopy (Kaftan et al, 2002;Sturgis et al, 2009;Sznee et al, 2011;Grzyb et al, 2013;Onoa et al, 2014), confocal laser scanning microscopy (Kowalewska et al, 2016;Mazur et al, 2019), and live cell imaging (Iwai et al, 2014;Iwai et al, 2016). The first scattering studies on photosynthetic membranes were performed in 1953 by Finean et al (1953) and has continued ever since.…”
Section: Introductionmentioning
confidence: 99%